SCALING UP POSITIVE PARENTING PRACTICES IN UGANDA: RESEARCH EVIDENCE FROM AN INTEGRATED COMMUNITY-LED INITIATIVE FOR REDUCING VIOLENCE AGAINST CHILDREN IN LIRA DISTRICT, NORTHERN UGANDA - Amollo, Mathew; Bosco Apota, John; Ahadwe Bangirana, Clare; Musika, Tom; Opobo, Timothy (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2022)
Community-based action research is increasingly gaining traction in development work, partly because of its benefits in contextualizing societal problems and “handing over the stick” to the communities; that is, researchers listen, question, and learn as the experts (the community members) identify their problems and define the change they desire. This research approach, therefore, empowers communities and is a shift from traditional research where the researcher presupposes that deductions about a phenomenon are to be made outside the natural environment. This research paper documents the use of participatory learning and action approaches in designing, implementing, and monitoring interventions to prevent violence against children in post-conflict northern Uganda, a region that suffered through the Lord’s Resistance insurgency from 1987 to 2006.